Simultaneous gains for negatively correlated traits of interest in plantain - Geferson Rocha Santos; Letícia Casseano de Souza Santos; Rafael Nunes de Almeida; Hércules dos Santos Pereira; Inês de Moura Trindade; Irany Rodrigues Pretti; Dimmy Herllen Silveira Gomes Barbosa; Edson Perito Amorim; Sávio da Silva Berilli; Ana Paula Candido Gabriel Berilli (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to identify negative correlations between phenotypic characteristics (agronomic and physicochemical) in plantain (Musa paradisiaca), and to evaluate selection indices to obtain simultaneous gains for agronomically relevant characteristics. Thirteen plantain genotypes were evaluated in a randomized complete block design with four replicates. Data on 16 agronomic and physicochemical traits were collected. Genotype dispersion regarding the set of traits was evaluated using the principal component analysis and the separation of dissimilarity groups via clustering (Mahalanobis distance). The genotypes were divided into four groups, in which genotypes 13 (commercial) and 9 (wild) formed isolated groups. Positive correlations between yield and plant height, in addition to negative correlations between these two and the content of soluble solids (SS) were identified. Taller plantain plants had the tendency to produce more, but with late fruit, which were more acid and had a lower SS content. Therefore, correlations between yield, plant height, and SS posed a challenge for the development of plantain cultivars. The index of Mulamba & Mock was applied, which allowed of obtaining simultaneous gains in the target traits. The multitrait selection indices are appropriate to identify plants that are shorter, more productive, and that have fruit with a higher SS contents.